MENINGKATKAN KEMAMPUAN MEMBACA TEKS BERITA DENGAN METODE PENAMPILAN MELALUI MEDIA TEKS BERJALAN PADA SISWA SMP NEGERI 2 TENGARAN - Makunti, Yesi (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2019)
Reading aloud skills can be applied in learning to read news texts. The purpose of this study is to improve students' reading learning and improve students' reading skills in news texts by using appearance method through running text media. This study uses a class action research design which is commonly called CAR. This classroom action research is carried out in four stages, namely planning, acting, observing, and reflecting. The results of this study indicated an increase in the ability to read news texts by using method of appearance through running text media. This increase can be proven based on the results of tests conducted by class VIII H students of Junior High School 2 Tengaran which includes cycle I tests and cycle II tests. The test results in the first cycle showed that the classical average value of reading news texts is 65.63. Then, in cycle II test, the classical average value of reading the news text reached 80.93. The increase in test results was also followed by a positive changes in students' behavior of class VIII H at Junior High School 2 Tengaran after learning to read news texts with appearance method through the running text media.